THE JUSTIFICATION OF THEORETICAL-METHODOLOGICAL FOUNDATIONS FOR THE EMPIRICAL RESEARCH ON ADOLESCENTS’ SELF-FULFILMENT - Kolomiiets, Lesia; Solvar, Viktoriia; Kozhedub, Tetiana (PSYCHOLOGICAL JOURNAL, 2019)
The article justifies the theoretical-methodological foundations for the empirical research on adolescents’ self-fulfilment. The article determines that adolescence is accompanied with strengthen self-reflection and ability to self-design, activation of self-determining and self-affirming processes, increase the need for self-development and self-realization; these processes require scientific attention in the context of studies on boys’ and girls’ self-fulfilment. National and foreign scientists’ approaches to definition of “personal self-fulfilment” were analyzed. By defining of the concept of “personal self-fulfilment”, the scientists emphasize an individual’s personal activities, his/her needs for self-realization and readiness for self-changes, creativity at fulfilment of diverse life tasks, his/her conscious need in fulfilment of personal potential and personal capacity development. The article determines that adolescents’ personal self-fulfilment should be understood as a conscious and continuous, endowed with signs of initiative activities, process of self-realization in life, which relies on self-determination, self-design, self-development, self-realization and self-actualization. Personal self-realization is accompanied by constant self-changes and self-improvements, determined by personal understanding of a life meaning and self-transcendence, own values and motivation attitudes. Personal self-realization is associated with the freedom of choices and accepted responsibility, achieved significant results in various areas of life-creation, relying on a person’s psychological resources and ability to use them effectively. A formal model is proposed that reveals the psychological content and structure of self-fulfilling through a set of its processes (self-determination, self-realization, self-actualization, self-development, etc.), forms (external and internal), components (motivational-value, acting-volitional, effective), determining a target point of personal self-fulfilment. Based on the performed theoretical analysis, the authors’ view on the components of adolescence’s personal self-fulfilment and its diagnostic indicators is offered, which will be studied in detail in the further empirical research.